Engaging children's voices for tourism and marine futures through drawing in Gili Trawangan, Indonesia - Kwong, Yim Ming Connie (Frontiers in Sustainable Tourism, 2024)
Ocean tourism is a primary source of income for many small-island and coastal communities. Participatory processes have been advocated to develop and implement community-based management plans to address various problems induced from tourism development and achieve the desired and sustainable futures. One debate over such processes is the under-representation of children. Using drawing workshops with children, this paper aims to explore children’s representations and temporal orientations towards the future of the marine environment of a tourist destination on Gili Trawangan in Indonesia. A total of 91 children participated in four drawing workshops in January 2023. They were asked to make two drawings based on the following broad questions: 1) What do you see/do at the sea and coast now? and 2) What do you want to see/do at the sea and coast 5 years later? They also attended a short interview to describe and explain what they had drawn. The children have represented uses of the sea and coast by themselves, other users as well as the marine animals. They have also expressed various temporal orientations through their drawings and interview, including anticipation, hope, expectation, concern, anxiety and despair. These temporal orientations offer a very strong set of information to be included in decision-making workshops and policy recommendations. This paper has reiterated that children do have a stake in such decision-making processes for their sustainable futures and thus their voices need to be heard. This paper is one of the attempts to provide opportunities for children to actively engage in research and have their voices heard through innovative methodologies. It is also the first attempt to explore children’s orientations towards the marine futures with the intent to include such information in the subsequent decision-making process. It adds to the existing literature by engaging children’s voices to promote inter-generational justice, and calls for increased efforts in the realisation of such component in sustainable development.